Ode to the city - an ethnographic drama - Blackledge, Adrian 1959-; Creese, Angela 1959- (Multilingual Matters, 2022)
This ethnographic drama script is adapted from observations conducted in a large city centre library in the UK. It is a creative curation of field notes, transcripts, audio recordings, video recordings, conversations, and observations. The ethnographic drama tells a story of political tension in everyday life at a time of austerity
Description based on online resource; title from PDF title page (publisher's Web site, viewed 29. Mrz 2022)
Keywords: Bilingualism & multilingualism; Migration, immigration & emigration; Research methods: general; LANGUAGE ARTS & DISCIPLINES / Linguistics / General; Intercultural communication -- England -- Birmingham -- Drama; Librarians -- Language -- England -- Birmingham -- Drama; Librarians -- England -- Birmingham -- Language -- Drama; Multilingualism -- England -- Birmingham -- Drama; Municipal government -- England -- Birmingham -- Drama